Uncovering Patterns of Italian Consumers' Interest for Gluten-Free Beers. (2nd October 2021) - Donadini, Gianluca; Bertuzzi, Terenzio; Rossi, Filippo; Spigno, Giorgia; Porretta, Sebastiano
Abstract: This study explored the interest for Gluten-Free Beer (GFB) in a panel of beer drinkers. The authors adopted a conjoint rating experiment and the respondents were given sixty-four beer concepts to evaluate and score on a 9-point scale of interest. Each concept included eleven factors (alcohol content, colour, type of malt, beer price, drinking location, drinking occasion, bottle size, label claims, type of farming, type of brewer, and bottle closure) varied at different levels. The results showed that the consumers placed greatest importance on alcohol content (30.8%), followed by beer colour (18.3%), price (13.8%), type of brewer (9.5%), drinking occasion (9.5%) and bottle closure (6.5%). The label claim "rich in" and the factors drinking location, malt type, bottle size, and type of farming were judged as being of little importance. Average consumers' interest for GFB was moderate (5.48 on a 9-point scale) and oriented towards a blond small-scale brewed beer with a %ABV > 7.0. This beer was priced in the 1.51-2.50 Euros range per 0.33 L bottle and was suitable for drinking in the evening after dinner. Differences in interest between genders, age classes, and patterns of beer consumption are reported and discussed. These results support new GFB development and ensure R&D processes are tailored to the target consumer.